A Case of an 80-Year-Old Man with Empyema and Psoas Abscess. (26th October 2020) - Sakurai, Mikio; Nagasawa, Hiroki; Takeuchi, Ikuto; Yanagawa, Youichi
Abstract : An 80-year-old man with flu symptoms collapsed at his house and had a backache worsened over time. His family called for an ambulance. On arrival, chest X-ray showed reduced permeability of the right lung field, and truncal computed tomography (CT) suggested right multilobular empyema and right iliopsoas abscess. A blood test showed an acute inflammatory response. The patient underwent right small thoracotomy for empyema and ultrasonic-guided drainage for the right iliopsoas abscess and started the administration of antibiotics. We started the administration of doripenem by intravenous drip and then deescalated to ampicillin based on the culture results. Streptococcus intermedius was cultured from all sites. Following these treatments for three months, his general condition improved. We herein report a unique case of complicated empyema and iliopsoas abscess in which a favorable outcome was obtained by an appropriate diagnosis and treatment. Reports of multiple abscesses have been increasing recently because of the growing geriatric population and aging-related complications. It is important to search the whole body to detect multiple abscesses in cases where an abscess is detected at a single site.